Piezoresistive effect of n-type ⟨111⟩-oriented Si nanowires under large tension/compression. (25th January 2017) - Gao, Di; Yang, Zhenyu; Zheng, Lingli; Zheng, Kun
Abstract: Small-scale samples enable us to understand changes in physical properties under larger strain due to their higher tolerance to deformation. In this study, the piezoresistive character of n-type ⟨111⟩-oriented Si nanowires under large strain was measured during tensile and compressive deformations. The Si nanowires were directly cut from the wafer using top-down technology and deformed while capturing their electrical properties inside a transmission electron microscope. The experimental results show that both tensile and compressive deformation enhanced their electrical transport properties. The piezoresistance coefficient is of the same order of magnitude as its bulk counterpart, but half as large, which may be attributed to a larger strain magnitude. We also studied the circulatory characteristics and influence of electron beam radiation. This study provided new physical insights into piezoresistive effects under large strain.